Hubungan antara perancangan perniagaan, sumber pembiayaan dan persekitaran luaran dengan prestasi perniagaan: Kajian empirical PKS di Malaysia - Mohd Saad, Rosli (2014)
This study was conducted to determine the significant relationships between business planning, sources of equity and debt financing and all planning activities such as assessment and strategy, involvement by managements, formal procedure, mission and aim and performance of SME firms in Malaysia. This study also aims to assess the moderating effect of the dynamic, hostile and munificence external environments on the relationships between business planning, sources of equity and debt financing and performance. Sixteen hypotheses were put forward for testing. The quantitative research design was employed and primary data samples of 177 SME firms were collected and analysed through multiple and hierarchical regression analysis to obtain the results. The findings of the study revealed that overall business planning, source of equity financing and all activities of business planning have significant relationships with firm performance. A dynamic external environment was found to have a moderate positive relationship between business planning and performance but a moderate negative relationship between source of debt financing and performance. The findings also revealed that munificence environment was found to have a moderate negative relationship between sources of equity and debt financing on performance. However, no moderating effect of the hostile environment was found in the relationship between business planning, sources of equity and debt financing on performance as well as the moderating effect of munificence environment on the relationship between business planning and performance. This study is expected to contribute to the existing literature with the new finding of business planning activities that affect performance. This study is also important for the management of SMEs and policy-makers to play crucial roles in implementing business planning, using the source of equity financing and operating in an appropriate environment. This study concluded with a discussion of the limitations and suggestions for future research